1994
DOI: 10.1104/pp.105.4.1255
|View full text |Cite
|
Sign up to set email alerts
|

A Low Molecular Mass Heat-Shock Protein Is Localized to Higher Plant Mitochondria

Abstract: When pea (Pisum sativum 1. var Douce Provence) plants are shifted from a normal growth temperature of 25'C up to 40'C for 3 h, a nove1 22-kD protein is produced and accumulates in the matrix compartment of green leaf mitochondria. HSP22 was purified and used as antigen to prepare guinea pig antiserum. The expression of HSP22 was studied using immunodetection methods.HSP22 is a nuclear-encoded protein de novo synthesized in heatstressed pea plants. The heat-shock response is rapid and can be detected as early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
50
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 26 publications
9
50
0
1
Order By: Relevance
“…So far, the only demonstration of homododecameric complexes within the plant smHSP family had been obtained from bacterial expression of PsHSPs 18.1 and 17.7, two heatinducible smHSPs from pea (Pisum sativum L.) leaves (Lee et al, 1995). Since plant smHSPs are often found as highmolecular-mass aggregates of 200 to 240 kD (Helm et al, 1993;Lenne and Douce, 1994;Osteryoung and Vierling, 1994;Jinn et al, 1995), our results further support the hypothesis, put forward by Lee et al (1995), that such aggregates consist typically of 12 subunits. Indeed, this quaternary structure has been previously proposed for mammalian a-crystallins (Tardieu et al, 1986), a protein group related to animal and plant smHSPs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…So far, the only demonstration of homododecameric complexes within the plant smHSP family had been obtained from bacterial expression of PsHSPs 18.1 and 17.7, two heatinducible smHSPs from pea (Pisum sativum L.) leaves (Lee et al, 1995). Since plant smHSPs are often found as highmolecular-mass aggregates of 200 to 240 kD (Helm et al, 1993;Lenne and Douce, 1994;Osteryoung and Vierling, 1994;Jinn et al, 1995), our results further support the hypothesis, put forward by Lee et al (1995), that such aggregates consist typically of 12 subunits. Indeed, this quaternary structure has been previously proposed for mammalian a-crystallins (Tardieu et al, 1986), a protein group related to animal and plant smHSPs.…”
Section: Discussionsupporting
confidence: 78%
“…Plant smHSPs are a structurally diverse protein family, and the members, with molecular masses between 15 and 30 kD, have been grouped into five major classes (for review, see Waters et al, 1996). In plant cells smHSPs have been localized to the cytoplasm (classes I and 11), ER, mitochondria, and chloroplast (Vierling, 1991;Helm et al, 1993Helm et al, , 1995Lenne and Douce, 1994;LaFayette et al, 1996). A recent phylogenetic analysis has revealed that gene duplication, sequence divergence, and gene conversion have been major events in the evolution of this protein group (Waters, 1995).…”
mentioning
confidence: 99%
“…This induction is consistent with a series of reports highlighting HSP22 mRNA and protein induction during environmental stress in plants (15,48) and the linkage of HSP22 induction with cross-tolerance of plants to other oxidative stresses (16). The signal for mitochondrial HSP upregulation has been investigated recently in maize plants and shown to likely originate from decreased mitochondrial membrane potential (22) rather than an oxidative pathway per se, suggesting that onset of respiratory deficiency is a key element in HSP22 and HSP70 induction.…”
Section: Impact Of Environmental Stress On Plant Mitochondriasupporting
confidence: 75%
“…For example, overexpression of the mitochondrial Mn-SOD can increase plant stress tolerance (13), and more recently, its knock-out in yeast resulted in the specific oxidation of an array of mitochondrial proteins in the absence of this enzyme (14). Induction of the mitochondrial HSP22 folding chaperones have been reported in response to varying oxidative stresses in plants (15,16), animals (17), and insects (18). Recently in Drosophila, overexpression of HSP22 has been shown to increase life span and resistance to oxidative stress (19), whereas underexpression decreases life span (20).…”
mentioning
confidence: 99%
“…containing nine or more subunits (2,6,7). In mammalian systems, phosphorylation of sHPS during heat stress is involved in reducing oligomerization (7)(8)(9), but phosphorylation has not been observed in plant sHSPs.…”
mentioning
confidence: 99%